Does HPV type affect the rate of positive surgical margin after cervical cone excision? - Purut, Yunus Emre; Akış, Serkan; Keleş, Erhan; Api, Murat; Kabaca Kocakuşak, Canan; Ceylan, Yasemin; Giray, Burcu; Uzun, Mine (BMJ Publishing Group, 2019)
[Abstract Not Available]
Keywords: HPV Type; Positive Surgical; Cervical Cone